Efforts to Improve Indonesian Learning Achievements by Applying The Collaboration Teaching Model on Fifth Grade Student SD Negeri 01 Semitau Lesson Year 2015/2016 - Eny Sri Utari (Universitas Tanjungpura, 2018)
The purpose of this research is to know: (1) The influence of collaboration methods on the learning outcomes of Indonesian class V students of State Elementary School 01 Semitau. (2) The benefits of collaborative methods in an effort to facilitate the understanding of students of Class V Elementary School 01 Semitau of Kapuas Hulu Regency on reading the main idea of drama text.This research uses action research for three rounds, each round consists of four stages: design, activity and observation, reflection, and revision. Target of this research Elementary School Semarang 01 Semitau District Semitau Kapuas Hulu Year 2015-2016. Data obtained in the form of observation, observation sheet of teaching and learning activities. From the analysis result, it is found that the school administration service has increased from cycle I to cycle III, that is cycle I (26%), cycle II (56%), cycle III (100%). The conclusions of this study are, (1) Daily test result after using learning method of Collaboration has increased significantly that is 85,83 whereas previously only 56,23. (2) Implementation of class action obtained data that student interest increase after held PTK in cycle I percentage of student interest is 68,45% after held PTK in cycle II become 100%. (3) After the classroom action research (PTK) using the Collaboration learning model in cycle I the percentage of students' activity is 68.45% in cycle II to 100%